COMMUNICATION ETHICS IBN MISKAWAIH AND ITS RELEVANCE TO THE SOLVING OF MORAL PROBLEMS IN INDONESIA - Muhammad Taufiq Harahap; Hasyimsyah Hasyimsyah Hasyimsyah; Suwardi Suwardi Suwardi (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
This research was in depth exploration of the concept of communication ethics and its relevance for the solving of the problems of Indonesian Moral formulated by IbnMiskawaih in his work The Tahdzib Al-Akhlak. In the study of communication science, these two things are interrelated. Communication ethics is an ethical standard for communicators and communicants in communication. From the topic above, there are several problems from the purpose of this study they are; knowing the views of IbnMiskawaih about ethics in terms of communication science perspective, knowing IbnMiskawaih's views on the ethics of verbal and non-verbal communication, knowing the view of IbnMiskawaih about the ethics of intrapersonal communication, Knowing IbnMiskawaih's views on the ethics of interpersonal communication, knowing IbnMiskawaih's view of the ethics of group communication, knowing IbnMiskawaih's view of the ethics of media communication, knowing IbnMiskawaih's view of the ethics of social communication, formulating the communication ethics of IbnMiskwaih and its Relevance for the solving of Moral problems in Indonesia. The research methodology was begun by putting the type of qualitative research with historical research and social research approaches to the study of excellent figures to explore the thoughts and views of a figure in the field. The figure intended here was IbnMaskawaih with descriptive method, which is a research procedure that produces the descriptive data in the form of written or oral words of the people and behave that can be observed directed at the background of individuals holistically that occurred in the past. The Tahdzib Al-Akhlak, the work of IbnMiskawaih contains and affirms communication ethics clearly and systematically. All the substance of the book was oriented to the communication ethics. The IbnMiskwaih writing has laid the verbal and nonverbal communication, intra-personal communication, interpersonal communication, group communication and also mass communication. In the context of the solving of morality problems in Indonesia, the communication ethics written by Ibn Miskawaih  in The Tahdzib Al-Akhlak was also became a strategic solution to be applied, moreover Indonesia is in the condition of multi dimensional moral degradation. The Tahdzib Al-Akhlak by Ibnmiskwaih contains thoughts and moral teachings that were based on the noble moral values, collaboration between the study of theoretical philosophy and practical guidance, where the segment of education and teaching were more prominent. So in this context, IbnMiskwaih communicated various thoughts as a solution approach. Firstly, moral degradation was changed through the education. Secondly, the importance of education for children and adults. Thirdly, a fair leader in order to prevent the nation's moral degradation due to the role of a just leader is needed. Fourthly, the government's attention to the society became as the father's relationship with his son. Fifthly, choose a good friend as an effort to prevent the moral degradation. Sixthly, social virtue was also an important step in the solution of nation degradation. Seventhly, maintain mental health. This step was also quite strategic in solving the nation's degradation. At least internally there is an attempt to prevent the soul from becoming healthy and not easily contaminated with bad behaviors that can cause moral degradation in congregation.Key Word:  Moral, Ethics, Communication of Tahdzib al-AkhlakdanIbnMiskawaih